Empowering Female Sewing Communities by Optimizing the Use of Fabric Scraps to Create Economically Valuable Products - Husnaini, Nani; Jumrah; Hajaroh, Siti (Unram Journal of Community Service, 2026)
This Community Service activity aims to provide training and assistance in empowering the women's sewing community through the optimal utilization of fabric scraps to create products of economic value in Adeng Hamlet. The method used in this community service activity is the Asset-Based Community Development (ABCD) method. The ABCD method prioritizes the utilization of the potential of a group of people or community around the area. The Asset-Based Community Development (ABCD) method has five key steps, including: Discovery, Dream, Design, Define, and Destiny. The achievement of the community service activity can be said to be very good. In addition to receiving a positive response from the community, the participants were also able to produce products from parca fabric with a higher economic value than before. The enthusiasm of the community was also evident from the 100% attendance of the participants who were punctual in attending this activity from the beginning to the end. This assistance activity was then reported and compiled as a form of accountability by the lecturers as facilitators of the activity, which is a manifestation of the Tri Dharma Perguruan Tinggi (Three Pillars of Higher Education) in the field of Community Service.